2007
DOI: 10.1890/06-1051
|View full text |Cite
|
Sign up to set email alerts
|

Soil Feedback of Exotic Savanna Grass Relates to Pathogen Absence and Mycorrhizal Selectivity

Abstract: Abstract. Enemy release of exotic plants from soil pathogens has been tested by examining plant-soil feedback effects in repetitive growth cycles. However, positive soil feedback may also be due to enhanced benefit from the local arbuscular mycorrhizal fungi (AMF). Few studies actually have tested pathogen effects, and none of them did so in arid savannas. In the Kalahari savanna in Botswana, we compared the soil feedback of the exotic grass Cenchrus biflorus with that of two dominant native grasses, Eragrosti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(65 citation statements)
references
References 48 publications
2
61
0
2
Order By: Relevance
“…We transplanted seven-week-old seedlings individually into pots (16 cm height, 21 cm diameter) containing growing medium (50% topsoil and 50% sphagnum peat moss) that were arranged in an unheated greenhouse. To reduce potential adverse effects of host-specific soil biota, we collected topsoil from fields where no Triadica grew [25][26][27]. Subsequently, we enclosed each seedling in a nylon mesh cage (100 cm height, 27 cm diameter) that was fitted tightly to the rim of each pot to exclude insect herbivores.…”
Section: Materials and Methods (A) Study Organismsmentioning
confidence: 99%
“…We transplanted seven-week-old seedlings individually into pots (16 cm height, 21 cm diameter) containing growing medium (50% topsoil and 50% sphagnum peat moss) that were arranged in an unheated greenhouse. To reduce potential adverse effects of host-specific soil biota, we collected topsoil from fields where no Triadica grew [25][26][27]. Subsequently, we enclosed each seedling in a nylon mesh cage (100 cm height, 27 cm diameter) that was fitted tightly to the rim of each pot to exclude insect herbivores.…”
Section: Materials and Methods (A) Study Organismsmentioning
confidence: 99%
“…Numerous soil microbes have been isolated from invasive plant species (Table 1). Soil biota can influence the alien plant invasion through direct and indirect mechanisms (Reinhart & Callaway, 2006;van der Putten et al, 2007). Assessment of shifts in the microbial communities and their subsequent influence on the competition between native and invasive plant species could provide a better understanding of post-invasion changes (Hawkes et al, 2005;Zhang et al, 2010).…”
Section: Interactions Between Soil Biota and Invasive Plantsmentioning
confidence: 99%
“…The influence of nematodes feeding on an invasive grass A arenaria showed that plant roots were colonized by feeding generalist and not by feeding specialist in the non-native regions (van der Putten et al, 2005). The invasive soil pathogens that affect the natural vegetation have been mostly reported from the forest and ornamental plants.…”
Section: Interactions Between Soil Biota and Invasive Plantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Plants associating with arbuscular mycorrhizal fungi are typically more competitive and better able to tolerate environmental stresses than are non-mycorrhizal or poorly colonized plants (Biermann and Linderman 1983, Daniell et al 2001, Bianciotto and Bonfante 2002, Vandenkoornhuyse et al 2002, Bonfante 2003, Brundrett 2004, DeBellis and Widden 2006, Greipsson and DiTommaso 2006, Parniske 2008, Shah et al 2010. AMF are also known to provide protection from a variety of microbial pathogens to their host plants (Newsham et al 1994, Borowicz 2001, Klironomos 2002, Pozo and Azćon-Aguilar 2007, Van der Putten et al 2007, Appoloni et al 2008, Mogg et al 2008, Krüger et al 2009, Wehner et al 2009). …”
Section: Introductionmentioning
confidence: 99%